Four men celebrating with champagne and a trophy - Owen & Moroney, OM; Kilkenny Association, KILK
Black and white group portrait photograph of four men celebrating by pouring champagne into a trophy cup. They are identified from handwritten notes on the back as: Sheamus Keating (tip + sect); P Hegarty (winner); Irish Centre Manager (Clare); and Quiz Master, Luke Kennedy (Sligo). Photograph by Owen & Moroney, copyright Owen & Moroney.